Glucose metabolic disorder in Klinefelter syndrome: a retrospective analysis in a single Chinese hospital and literature review - Liu, Shixuan; Yuan, Tao; Song, Shuoning; Chen, Shi; Wang, Linjie; Fu, Yong; Dong, Yingyue; Tang, Yan; Zhao, Weigang (BMC endocrine disorders, 2021)
We aimed to investigate the clinical characteristics and islet β-cell function in patients with Klinefelter syndrome (KS) and hyperglycemia. This is a retrospective study. In total, 22 patients diagnosed with KS were identified from the electronic medical record system, including 9 patients with hyperglycemia (total patients with hyperglycemia, THG-KS group) and 5 hyperglycemic KS patients with oral glucose tolerance test (OGTT) results (HG-KS group). An additional 5 subjects with hyperglycemia and 5 normal glucose tolerance (NGT) subjects matched based on body mass index were included as the HG group and NGT group, respectively. Data from clinical and laboratory examinations were collected. We further performed a literature review of KS and hyperglycemia. We found that KS patients developed abnormal glucose metabolism earlier in life than those without KS, and the median age was 17 years, ranging from 10 years to 19 years. Six of 17 (35.3%) patients were diagnosed with diabetes mellitus and 3 of 17 (17.6%) patients were diagnosed with prediabetes. Among 10 patients with both fasting blood glucose and insulin results recorded, there were 8 out of 17 (47.1%) KS patients had insulin resistance. The prevalence of hypertension and dyslipidemia was higher in patients with hyperglycemia and KS than in patients with NGT KS. Compared with the HG group, insulin sensitivity levels were lower in HG-KS group, whereas homeostasis model assessment of β-cell function levels (p = 0.047) were significantly, indicating higher insulin secretion levels in the HG-KS group. KS patients develop hyperglycemia earlier in life than those without KS and show lower insulin sensitivity and higher insulin secretion. These patients also have a higher prevalence of other metabolic diseases and may have different frequencies of developing KS-related symptoms.